Psychiatric diagnoses as grounds for disability pension among former child welfare clients - Bask Miia; Ristikari Tiina; Hautakoski Ari; Gissler Mika (Society for Longitudinal and Life Course Studies, 2022)
This study used the 1987 Finnish Birth Cohort, which included all children born in Finland in 1987 (N=59,476), to investigate psychiatric diagnoses as grounds for disability pensions (DPs) among child welfare clients and explored the background factors associated with such diagnoses. Descriptive statistics show that DP is substantially more common among child welfare clients than among other children.
Logistic regressions revealed that the factors most strongly related to psychiatric diagnoses among girls were mother’s somatic DP, child protection history, and parental social assistance. Psychiatric diagnoses among boys were most strongly related to mother’s psychiatric DP, child protection history, and parental divorce.
The factors related to DP among girls included child protection history, father’s psychiatric DP, father’s somatic DP, and parental social assistance. DP among boys was related to child protection history, mother’s psychiatric DP, parental social assistance, father’s somatic DP, and father’s psychiatric care in specialised hospitals.
A child welfare history that includes out-of-home care indicates that there were severe problems in the home environment during upbringing. Detailed investigations should therefore be undertaken, such as examining the role of mediating and moderating factors, including the ability of social and educational services to ameliorate the effects of challenging childhood conditions.